2012
DOI: 10.1021/ic300278v
|View full text |Cite
|
Sign up to set email alerts
|

Trialkylphosphine-Stabilized Copper(I) Gallium(III) Phenylchalcogenolate Complexes: Crystal Structures and Generation of Ternary Semiconductors by Thermolysis

Abstract: A series of organometallic trialkylphosphine-stabilized copper gallium phenylchalcogenolate complexes [(R(3)P)(m)Cu(n)Me(2-x)Ga(EPh)(n+x+1)] (R = Me, Et, (i)Pr, (t)Bu; E = S, Se, Te; x = 0, 1) has been prepared and structurally characterized by X-ray diffraction. From their molecular structures three groups of compounds can be distinguished: ionic compounds, ring systems, and cage structures. All these complexes contain one gallium atom bound to one or two methyl groups, whereas the number of copper atoms, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The SSPs of the type [(PR 3 ) n Cu I (μ‐ER′) 2 M III (ER′) 2 ] (M=Ga, In; R, R′=alkyl, aryl) have been thoroughly investigated for the preparation of chalcopyrite thin film using chemical vapour deposition technique. The organic groups attached to P and E atoms are responsible not only for the structural variation but also the deposition behaviour in the thermolysis process of the precursors . Very often the isolation of such SSPs may be inherently difficult due to instability, non‐formation of bimetallic bridge “Cu(μ‐ER′) 2 In”, or rapid polymerization of the precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The SSPs of the type [(PR 3 ) n Cu I (μ‐ER′) 2 M III (ER′) 2 ] (M=Ga, In; R, R′=alkyl, aryl) have been thoroughly investigated for the preparation of chalcopyrite thin film using chemical vapour deposition technique. The organic groups attached to P and E atoms are responsible not only for the structural variation but also the deposition behaviour in the thermolysis process of the precursors . Very often the isolation of such SSPs may be inherently difficult due to instability, non‐formation of bimetallic bridge “Cu(μ‐ER′) 2 In”, or rapid polymerization of the precursors.…”
Section: Introductionmentioning
confidence: 99%
“…reported the synthesis of Ga 2 S 3 and In 2 S 3 nanoparticles by thermally induced destruction of [MeM(SCH 2 CH 2 S)]n (M=Ga, In), that had been shown as suitable SSP despite its polymeric nature. The above mentioned polymers are also suitable starting compounds for the synthesis of [(R 3 P) m Cu n Me 2− x Ga(EPh) n + x +1 ] (R=Me, Et, i Pr, t Bu; E=S, Se, Te; x= 0, 1) that were used as SSPs for the preparation of ternary CuGaE 2 semiconductors . However, all these studies also revealed that synthesis of monomeric chalcogenolates of group 13 elements is rather problematic.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned polymers are also suitables tarting compounds for the synthesis of [(R 3 P) m Cu n Me 2Àx Ga(EPh) n + x + 1 ]( R = Me, Et, iPr, tBu;E = S, Se, Te ; x = 0, 1) that were used as SSPs fort he preparationo f ternary CuGaE 2 semiconductors. [17] However,a ll these studies also revealed that synthesis of monomeric chalcogenolates of group 13 elements is rather problematic.T he Lewis acidic metal centrumisusually involved in intermolecularE!Minteractions,w hich providet heir polymerics tructures making these compounds low volatile and hardly soluble in common organic solvents, therefore unfavorable for SSPs. In 1984, Hofmann [18] et al showed that simple addition of externalL ewis base NMe 3 to the polymericg allium thiolates Ga(SR) 3 (R = CH 3 ,C 2 H 5 , nPr, iPr,P h, CH 2 Ph) provides the monomeric complexes Ga(SR) 3 ·NMe 3 .L ater on, the concept of intramolecular P!Ga interaction stabilized monomeric complex Me 2 Ga{(SC 6 H 4 -2-PPh 2 )-k 2 S,P} ( Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular precursors are usually stabilized by phosphine ligands coordinating the copper atoms, to prevent uncontrolled oligomerization, and to provide solubility in organic solvents. These ligands are released during the thermal decomposition process, producing the semiconductor material 1b,f,g,i,p,q. 2 Due to its commercial availability, triphenylphosphine has been commonly used for this purpose 1b,c,f,g,i,ln,o.…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to its commercial availability, triphenylphosphine has been commonly used for this purpose 1b,c,f,g,i,ln,o. However, we use trialkylphosphines instead, because they are more volatile, more easily soluble in organic solvents, and provide the possibility to tune their steric demand by varying the size of the alkyl groups, thereby influencing the structure and composition of the complexes, and their thermolysis behavior 1p…”
Section: Introductionmentioning
confidence: 99%